Equações de estimativa do crescimento do sistema radicular e produção de fitomassa de alface hidropônica - Borcioni, Elis (2008)
Modelling is a technique that can be used to understand interactions between plant and environment, such as hydroponic growth dynamics. The study objective was to adjust models to estimate hydroponic lettuce growth, with emphasis on root system, the plants ware produced under different irrigations intervals. It was also verified the dynamics of interaction between root growth and nutrient solution retention for a better handling of irrigation management. Six experiments were carried out from September 2006 to September 2007 in plastic greenhouse, with an area of 250 m2 located at Fitotecnia Department of Federal University of Santa Maria, Rio Grande do Sul, Brazil. The cultivar used was Regina belonging to the group of loose smooth leaves which presents high resistance to early bolting. Growth analyses were performed on a five days interval where nutrient solution retention, root length and volume were all measured. The models were fitted using days after transplant (DAT), degree day (GD) and effective thermal index (GDE) variables. The model performance evaluation was carried out using confidence index. Regardless of the time of the year and the used variable, linear models showed very good performance in estimating dry phytomass. More complex models with a large number of coefficients showed similar performance to the linear ones. Linear models also showed better performance for estimating root length. However, the application of GD and GDE variables improved estimates of roots length and volume. Results showed that increase in root volume increase nutrient solution retention, proving that the root system acts as a barrier to the proper flow of the nutrient solution.